2014
DOI: 10.1186/1471-2407-14-154
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-stroma metabolic relationship based on lactate shuttle can sustain prostate cancer progression

Abstract: BackgroundCancer cell adopts peculiar metabolic strategies aimed to sustain the continuous proliferation in an environment characterized by relevant fluctuations in oxygen and nutrient levels. Monocarboxylate transporters MCT1 and MCT4 can drive such adaptation permitting the transport across plasma membrane of different monocarboxylic acids involved in energy metabolism.MethodsRole of MCTs in tumor-stroma metabolic relationship was investigated in vitro and in vivo using transformed prostate epithelial cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 33 publications
3
77
0
Order By: Relevance
“…Group 1, patients with no unfavorable genotypes; Group 2, those with one unfavorable genotype; Group 3, those with two unfavorable genotypes; Group 4, those with three unfavorable genotypes (Gerlinger et al 2012;Lee et al 2012) and poor prognosis of patients (Gerlinger et al 2012;Halestrap 2013;Miranda-Goncalves et al 2013;PertegaGomes et al 2011;Zhu et al 2014). Besides MCT molecules in tumor cells, recent studies have demonstrated that MCTs expressed on tumor and stroma cells mediate a lactate shuttle, which prevent lactate accumulation in tumor microenvironment and promote the survival, proliferation and progression of cancer cells (Sanita et al 2014;Vegran et al 2011). Therefore, the MCTs may be useful biomarkers for prognosis prediction and a potential therapeutic target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Group 1, patients with no unfavorable genotypes; Group 2, those with one unfavorable genotype; Group 3, those with two unfavorable genotypes; Group 4, those with three unfavorable genotypes (Gerlinger et al 2012;Lee et al 2012) and poor prognosis of patients (Gerlinger et al 2012;Halestrap 2013;Miranda-Goncalves et al 2013;PertegaGomes et al 2011;Zhu et al 2014). Besides MCT molecules in tumor cells, recent studies have demonstrated that MCTs expressed on tumor and stroma cells mediate a lactate shuttle, which prevent lactate accumulation in tumor microenvironment and promote the survival, proliferation and progression of cancer cells (Sanita et al 2014;Vegran et al 2011). Therefore, the MCTs may be useful biomarkers for prognosis prediction and a potential therapeutic target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…An other study showed that prostate can cer cells can redi rect the me tab o lism of ad ja cent fi brob lasts to wards a gly colytic phe no type. The sub se quent re lease of lac tate by fi brob lasts in turn pro moted prostate tu mor growth [81].…”
Section: Metabolic Cooperation In Cancermentioning
confidence: 99%
“…Prostate carcinoma cells induce glycolysis in fibroblasts and this glycolysis and lactate extrusion drives OXPHOS in carcinoma cells 167,174 . In ovarian cancer, adipocytes transfer free fatty acids (FFAs) via fatty acid-binding protein 4 (FABP4) to carcinoma cells 175 .…”
Section: Tumour Metabolismmentioning
confidence: 99%